Влияние организационной культуры на трансфер знаний в рамках осуществления стратегии «один пояс - один путь»: Пример китайских компаний, участвующих в Китайско-Пакистанском Экономическом Коридоре (CPEC) - МухаммедС.; ГириР.; МададА.; АсанА. (Вопросы государственного и муниципального управления, 2019)
The purpose of this paper is to investigate the relationship between organizational cultural characteristics, knowledge transfer and the role of certain identified organizational cultural aspects in the execution of knowledge transfer in Chinese Multinational Companies involved in CPEC. A quantitative research plan was followed. A questionnaire was used to collect the desired data. For this study we identified six factors, including trust among colleagues, communication between organizational staff, information systems, formation of the reward system, and structure of the organization which plays an important and defining role in the interaction between staff members and in providing possibilities to sever barriers to knowledge transfer. A total of 27 organizations involved in the China Pakistan Economic Corridor (CPEC) are identified. The intended hypothesis was tested by using PLS-SEM, and our research finding indicates that all the variables except information systems did not show positive relationships. The study proposed that multinational organizations must understand the critical role of organizational culture and interaction among team members in promoting, sharing, and spreading knowledge to perform well and achieve organizational success thereafter. This study is anticipated to help Chinese MNCs in Pakistan to understand the different cultural characteristics because according to previous studies many multinational companies overlook the impact of culture factors on the sharing of knowledge, while bearing in mind that in the literature there is no specific study regarding Chinese MNCs involved in CPEC. The conclusion of this study will help out knowledge executives charged with the drawing of flexible knowledge management systems.